2022
DOI: 10.3390/ijms23020730
|View full text |Cite
|
Sign up to set email alerts
|

Combination of NOS- and PDK-Inhibitory Activity: Possible Way to Enhance Antitumor Effects

Abstract: We have previously demonstrated a high antitumor potential of NOS inhibitor T1023 (1-isobutanoyl-2-isopropylisothiourea hydrobromide): antitumor antiangiogenic activity in several animal tumor models and its ability to synergistically enhance the antitumor effects of bevacizumab, cyclophosphamide and γ-radiation. At the same time, rather rapid adaptation of experimental neoplasias to T1023 treatment was often observed. We attempted to enhance the antitumor activity of this NOS inhibitor by supplementing its mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This multifunctionality enabled T1084 to concurrently exert two distinct pharmacological actions, anti-angiogenesis and hypoxia-oriented cytotoxicity, that could potentially enhance its anti-tumor effects. The methodology employed in this study potentially allowed for the possibility of developing additional multifunctional anti-tumor compounds with diverse molecular mechanisms of action [105].…”
Section: Small Moleculesmentioning
confidence: 99%
“…This multifunctionality enabled T1084 to concurrently exert two distinct pharmacological actions, anti-angiogenesis and hypoxia-oriented cytotoxicity, that could potentially enhance its anti-tumor effects. The methodology employed in this study potentially allowed for the possibility of developing additional multifunctional anti-tumor compounds with diverse molecular mechanisms of action [105].…”
Section: Small Moleculesmentioning
confidence: 99%
“…So, some time ago, while screening linear and cyclic isothioureas, we identified and synthesized a large group of isothiourea derivatives (Figure 1A) that are competitive inhibitors of NOS (Proskuryakov et al, 2002(Proskuryakov et al, , 2005Proskuryakov et al, 2010;Filimonova et al, 2012a). Further, we found that some compounds of this group (such as T1023, T1082, T1084) are promising for further pharmacological development-as hypoxic radioprotectors that provide effective prevention of hematopoietic and gastrointestinal acute radiation syndromes, and radiotherapy complications (Filimonova et al, 2020b(Filimonova et al, , 2021(Filimonova et al, , 2022bSaburova et al, 2020), as well as antitumor, antiangiogenic agents (Filimonova et al, 2019a;2019b;2022a).…”
Section: Introductionmentioning
confidence: 99%